The role of extracorporeal CO2 removal from pathophysiology to clinical applications with focus on potential combination with RRT: an expert opinion document - Parrilla-Gómez, Francisco José; Castelli, Antonio; Colombo, Riccardo; do Vale-Fernandes, Antero; Nalesso, Federico; Pestaña-Lagunas, David; Suarez-Sipmann, Fernando; Terragni, Pierpaolo (Frontiers in Medicine, 2025)
Technological advancements have facilitated the application of extracorporeal-carbon-dioxide removal (ECCO2R) in managing acute respiratory-failure (ARF), including both hypoxemic and hypercapnic forms. A non-systematic literature review (PubMed, Medline, Embase, Google Scholar; January 2000–November 2024) identified randomized-controlled-trials (RCTs) and real-world evidence (RWE) on ECCO2R, alone or combined with continuous renal replacement therapy (CRRT). A multidisciplinary panel of intensivists, anesthesiologists, and nephrologists from Italy, Portugal, and Spain assessed clinical integration of ECCO2R. Key considerations included identifying ideal candidates, such as patients with acute respiratory distress syndrome (ARDS), chronic obstructive pulmonary disease (COPD), asthma exacerbations, alongside initiation timing and discontinuation criteria. For ARDS, recommended initiation thresholds included driving pressure ≥15 cm H2O, plateau pressure ≥28 cm H2O, pH < 7.28, and respiratory-rate >25 breaths/min. In COPD or asthma exacerbations at risk of non-invasive ventilation (NIV) failure, triggers included pH ≤ 7.25, RR ≥ 30 breaths/min, Intrinsic-PEEP ≥ 5 cm H2O, signs of respiratory fatigue, paradoxical abdominal motion, and severe distress. Absolute contraindications were uncontrolled bleeding, refractory hemodynamic instability, or lack of vascular access. Relative contraindications included moderate coagulopathy and limited access. The panel concluded ECCO2R may support selected adults with ARDS or obstructive lung disease, though further RCTs and high-quality prospective studies are needed to guide practice.